Microbiological and Physical Changes Produced by Different Air–Powders on Contaminated Titanium Implant Surfaces: An In Vitro Pilot Study - Samy Francis; Vito Carlo Alberto Caponio; Francesca Spirito; Vittoria Perrotti; Alessandro Quaranta (Applied Sciences, 2023)
Air–powder abrasive treatment has shown interesting results for dental implant treatments; however, which powder is most effective is still an open question. This in vitro pilot study aims to compare the ability of six different powders (sodium bicarbonate powder—65 µm and 40 µm; glycine powder; erythritol powder—with and without cetylpyridinium chloride and calcium carbonate) to remove biofilm from contaminated titanium discs and to evaluate the physical effects of such treatments on surface topography. Seventy-four titanium discs with two different surface roughness were treated after S. sanguinis contamination. Cleaning ability and surface changes were assessed by scanning electron and confocal laser scanning microscopy as well as profilometry. All treated surfaces showed minimal bacterial residues compared to untreated ones, regardless of the treatment provided (remaining biofilm range 11.4% to 28.4% on machined discs—range 10.7% to 18.3% on moderately rough surface discs). No relevant changes on the microscopic ultrastructure of the disc surfaces were noted. The different treatments reduced biofilm up to 89.3 and 88.6% on moderately rough and machined discs, respectively, and they all showed statistically significant superiority over calcium carbonate powder. None of the tested treatments rendered the disc surfaces biofilm-free. Therefore, combined mechanical and chemical decontamination methods are still recommended to achieve maximum biofilm removal for peri-implantitis treatment.